Analisis Faktor Keberhasilan Membaca Permulaan Siswa Kelas I Sekolah Dasar - Hasnatul Fadhilah; Chandra Chandra; Inggria Kharisma (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research aims to analyze the initial reading ability of grade I students at elementary school and the success factors in beginning reading. Initial reading is the initial stage that a person does before being able to reach a higher level of reading. This study uses a qualitative method with results described descriptively. Data collection was carried out using tests, interviews, and observations. The result of this study is that the level of initial reading ability of grade I students of elementary school is in the very good category. This success is supported by the start of early reading from PAUD or TK, advanced reading exercises in elementary schools, the role of classroom literacy corners, and parental support.